2014
DOI: 10.1177/1359105314547752
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of psychological distress and interest in mental health services in individuals with cancer

Abstract: OBJECTIVE Identifying risk factors for psychological distress in patients with cancer may help providers more efficiently screen, identify, and manage distress. The present paper presents predictors of psychological distress in a large heterogeneous sample of cancer patients. METHODS 836 patients were enrolled in a large RCT and completed computerized psychosocial assessments (MHADRO). RESULTS Multivariate regressions examined predictors of distress and interest in mental health services. Final models sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 22 publications
4
17
1
Order By: Relevance
“…It has been established that cancer patients experience severe psychological distress from the time of diagnosis to the completion of treatment. [26][27][28] As supported by the qualitative findings of this study, distress could be the reason for not being able to quit this habit. A majority of our patients reported a lower level of nicotine dependence and still found it difficult to quit.…”
Section: Discussionmentioning
confidence: 67%
“…It has been established that cancer patients experience severe psychological distress from the time of diagnosis to the completion of treatment. [26][27][28] As supported by the qualitative findings of this study, distress could be the reason for not being able to quit this habit. A majority of our patients reported a lower level of nicotine dependence and still found it difficult to quit.…”
Section: Discussionmentioning
confidence: 67%
“…Older age was significantly related to psychosocial distress among non-immigrant nurses but not among immigrant nurses, whereas the relationship was negative but not significant. Various studies have reported that the correlation between age and psychosocial stress can either be positive [64][65][66] or negative [67][68][69]. Responsibilities, such as caring for family members or having financial liabilities, like paying off loans, explain higher levels of stress among younger people [64].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported that the correlation between age and psychosocial stress can either be positive [64][65][66] or negative [67][68][69]. Responsibilities, such as caring for family members or having financial liabilities, like paying off loans, explain higher levels of stress among younger people [64]. On the other hand, prolonged life expectancy can be related to facing more health-related stressors, thus leading to higher levels of perceived stress [70,71].…”
Section: Discussionmentioning
confidence: 99%
“…It is recommended high risk patients be identified for psychological morbidities and screening be improved to provide quick, cost effective psychological interventions via online platforms to manage symptoms during the COVID-19 pandemic [ 91 ]. In addition, considering the lack of time and resources for personalized screenings, We recommended programs such as Mental Health and Dynamic Referral for Oncology (MHADRO) to assist with screening for mental health problems for cancer patients [ 92 ]. Therefore, It is necessary to provide health services to cancer patients during COVID-19 pandemic, in order to prevent the predictable decline of cancer conditions, and prevent health system overload and health control crisis.…”
Section: Discussionmentioning
confidence: 99%